PENGARUH PERSEPSI KEMUDAHAAN DAN PERSEPSI MANFAAT TERHADAP NIAT PENGGUNAAN TEKNOLOGI KEUANGAN SEBAGAI ALAT PEMBAYARAN - Sijabat, Yacobo P; Hirawati, Heni; Giovanni, Axel (Jurnal Riset Entrepreneurship, 2020)
The technology applied by companies in transactions must pay attention to aspects of behavior. Researchers use the Technology Acceptance Model (TAM) as the main model of research. The researcher's goal is to determine the effect of several Technology Acceptance Model (TAM) variables on the intention to use financial technology as a means of payment. The data used by researchers are data from 118 students of the Faculty of Economics, Tidar University. Researchers use primary data by distributing questionnaires to students to determine the effect of each variable studied. The validity test used by researchers is the Corrected Item-Total Correlation value, while for the reliability test the Cronbach Alfa Test is used. Researchers use multiple linear regression methods in analyzing data and variables. Researchers found that the effect of perceived ease of use and perceived benefits on the intention to use financial technology in simultaneous transactions and had a significant effect. Likewise, partially, for each variable influences the intention to use financial technology in transactions and reliability.